A határmentiség regionális sajátosságainak vizsgálata Románia Észak-nyugati fejlesztési régiójában, különös tekintettel Bihar megyére - Kutasiné Nagy, Irén; Harsányi, Endre (Közép-Európai Közlemények, 2015)
The study is about the North-Western development regions of Romania, and also the spatial, social and economic development of Bihor county is analysed. Spatial disparities are shown compared to the EU-27, the member state volume index and to the national and region average. The differences amongst the economic performance of the eight Romanian development regions have been increased during 2000–2010. While in 2000 the differences between the GDP of the weakest and best performing regions have been 69.23% and 215%, it increased to 63 and 241% by 2010. Half of the GDP per capita of the EU-27 average has been exceeded only by one region (Western: 53%), the rest of the regions remained below that; only Bucharest-Ilfovi was above the 100% of the EU-27 average. According to the 2014–2020 development period, and the new region classification (based on the GDP percentage of the EU-27 average) seven Romanian regions are considered less developed and one of them is developed. In total, the economic performance of all six counties of the North-Western region has increased, but balanced, significantly high development was realised only in Kolozs county as a region centre (130% development). The economic catching up process as so far accompanied by the increase of regional inequalities. The employment of the county by national economy sectors shows that the ratio of people working in agriculture is high (33% of the total employed). Strengthening of the regional cohesion requires the following: catching up of regions, development of new economic structure, knowledge demanding activities, advancement of economic services. The success of catching up within the region and the county depends on the level of human capital and training structure by means of which high economic growth and dynamic regions can be formed.